LANGUAGE STYLE ANALYSIS OF ROBERT FROST POEM CALLED “THE SOUND OF TREES” IN MOUNTAIN INTERVAL COLLECTION - Ratri Dwiningtyas Malik; Aulia Putri; Sri Langgeng Ratnasari; Linayati Lestari; Gandhi Sutjahjo (JURNAL DIMENSI, 2023)
The purpose of this study is to analyze the language style in Robert Frost’s poem called "The Sound of Trees" in terms of frozen style, formal style, consultative style, casual style and intimate style. This poem is viewed from sociolinguistics study analysis by using Martin Joos theory as a guide to analyse the language style in Robert Frost’s poem. This study used descriptive method to analyze the data. Frozen language style used in an important document, in court also reciting a pledge. Formal style follows the speech most recognized by people in society. It is used when one in a particular place or situation. Consultative language style aims by the person between strangers, person to person without using slangs. This type of style stills has boundaries and limit in which who is someone talking to. Casual style can be used with acquaintance or the person you just meet. Intimate style frequently used in term when a person already know the target person. It can be between family members, couples and close friend.